Physical Handles at the Interactive Surface: Exploring Tangibility and its Benefits - Terrenghi, Lucia; Kirk, David; Richter, Hendrik; Kramer, Sebastian; Hilliges, Otmar; Butz, Andreas (Proceedings of the working conference on Advanced visual interfaces, 2008)
In this paper we investigate tangible interaction on interactive tabletops. These afford the support and integration of physical artefacts for the manipulation of digital media. To inform the design of interfaces for interactive surfaces we think it is necessary to deeply understand the benefits of employing such physical handles, i.e., the benefits of employing a third spatial dimension at the point of interaction. To this end we conducted an experimental study by designing and comparing two versions of an interactive tool on a tabletop dis-play, one with a physical 3D handle, and one purely graphical (but direct touch enabled). Whilst hypothesizing that the 3D version would provide a number of benefits, our observations revealed that users developed diverse interaction approaches and attitudes about hybrid and direct touch interaction.